Combined Stress - Pitarresi, James (McGraw-Hill's AccessEngineering., 2012)
This video illustrates an example in Roarks' Formulas for Stress and Strain on combined stress. The example shows how to determine the maximum tensile stress and the maximum shear stress of a pipe subject to an internal pressure and a twisting m